Fijimycins A–C, three antibacterial etamycin-class depsipeptides from a marine-derived Streptomyces sp. - Sun, Peng (2011)
Three new depsipeptides, fijimycins A–C f(1–3), together with the known etamycin A (4), were isolated and identified from the fermentation broth of strain CNS-575, a Streptomyces sp. cultured from a marine sediment sample collected off Nasese, Fiji. The planar structures of the new fijimycins were assigned by combined interpretation of NMR and MS/MS spectroscopic data. These assignments were complicated by the fact that 1–3 occurred as complex amide conformational mixtures. The absolute configurations of the component amino acids were established using the Marfey’s method. Fijimycins A–C, and etamycin A, were shown to possess significant in vitro antibacterial activity against three methicillin-resistant Staphylococcus aureus (MRSA) strains with MIC(100) values between 4–16 µg/mL.